Labour's aims in war and peace - Attlee, Clement; Noel-Baker, Philip; Woolf, Leonard; Laski, Harold J. (London : Lincolns-Prager)
Bibliotheek Camille Huysmans
Engels
Monografie
Keywords: Labour Party; Wereldoorlog 2; Groot-Brittannië.